Pemodelan Kausal Pengaruh Tingkat Suku Bunga dan Inflasi terhadap IHSG di BEI - Sri Hasnawati; Ernie Hendrawaty; Arivina Ratih Yulihar Taher; Skolastika Elvira Emma Riyadi; Fidelys Grecia Hutabarat; Kamadie Sumanda Syafis (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: The purpose of this study is to see whether there are direct and indirect effects of inflation to interest rates, and also to see the direct and indirect relationship between inflation and interest rates to the IHSG using path analysis for the period January 2016 to July 2022. Research Methodology: To answer the research objectives, a path analysis model was used. This study uses time series data during January 2016 to July 2022 Result: The results of the study This study finds that there is a direct effect between inflation and interest rates. However, this study did not find a direct effect of inflation on the IHSG. In this study, joint testing found that interest rates and inflation had a direct effect on the IHSG.